INFLUENCE THE PROPOTION OF INDEPENDENT DIRECTORS AND CONTROLING SHAREHOLDERS ON THE EARNINGS MANAGEMENT - pedi riswandi (Universitas Prof.Hazairin,SH Bengkulu, 2019)
Manager's motivation to do earnings management to good financial statements by presenting misleading information to stakeholders, so that the Board of Commissioners is important to supervise effectively the company's operations control with controlling shareholders.This study aimed to determine if the proportion of the independent director and the ownership of the controlling share may reduce earnings management. This research uses manufacturing companies Indonesia in 2012-2016. The technique of purposive sampling method. The results showed that the proportion of proportion of the independent directors and controlling shareholders reduce the occurrence of profit management